2003
DOI: 10.1080/713673166
|View full text |Cite
|
Sign up to set email alerts
|

The Demand for Military Spending in Developing Countries

Abstract: Numerous studies have estimated demand for military expenditure in terms of economic, political and strategic variables. Ten years after the end of the Cold War, this paper attempts to ascertain if the new strategic environment has changed the pattern of determinants, by estimating cross-country demand functions for developing countries for periods during and just after the Cold War. The results suggest that, for both periods, military burden depended on neighbours' military spending and internal and external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 13 publications
7
87
0
3
Order By: Relevance
“…To capture this a total trade variable (Trade), imports plus exports, was included. Dunne and Perlo-Freeman (2003) used the above model to estimate cross-section regressions for the demand for military expenditure during and after the Cold War. This tells us a lot about the differences in military burden between countries, but gives no information about the dynamics of the process.…”
Section: Modelling the Demand For Military Spendingmentioning
confidence: 99%
See 1 more Smart Citation
“…To capture this a total trade variable (Trade), imports plus exports, was included. Dunne and Perlo-Freeman (2003) used the above model to estimate cross-section regressions for the demand for military expenditure during and after the Cold War. This tells us a lot about the differences in military burden between countries, but gives no information about the dynamics of the process.…”
Section: Modelling the Demand For Military Spendingmentioning
confidence: 99%
“…The number of external conflicts has greatly diminished, while civil wars have proliferated, fuelled by ethnicity, religion and control of resources (Kaldor, 1999;Collier and Hoeffler, 1998). Dunne and Perlo-Freeman (2003) was one of the first studies to re-examine the empirical picture using data from after the end of the Cold War, to assess whether this dramatic change in the global strategic environment had altered the pattern of demand for military spending. Using a cross-section model incorporating economic, political and strategic variables, they estimated demand functions for two separate periods, one in the 1980s, and one in the 1990s, after the fall of the Berlin Wall.…”
Section: Introductionmentioning
confidence: 99%
“…These are issues that are not necessarily easy to express in monetary terms, but are important to include in any conflict cost calculation. Smith (1989) Neither Smith (1989), nor Dunne and Perlo-Freeman (2003) attempt to analyse the influence of military expenditure on the growth of GDP, but there are authors who have attempted to do so. Table 2 shows the different channels through which it is hypothesised that conflict can influence the economy.…”
Section: Indirect Effectsmentioning
confidence: 99%
“…Lastly, population variable is incorporated to confine possible size effects. Dunne and Perlo-Freeman (2001) stated that it may be seen as giving some intrinsic security, reducing the need for military expenditure, or may reduce costs by allowing reliance on a large army rather than hi-tech equipment. On the other hand "public good" theory would suggest that a high population makes military spending more effective, as it benefits a larger number of people as a "pure public good".…”
Section: Motivation For Some Variables Usedmentioning
confidence: 99%
“…The study also indicated the importance of GDP per capita and wars as determinants of military expenditure in Southern Africa. Dunne and Perlo-Freeman (2001) undertakes a study in an attempt to evaluate the driving forces behind military spending in developing countries by comparing a period during the Cold War with the period afterwards. Their study is concerned with developing economies and is particularly concerned with the impact of changes in security webs on military spending.…”
Section: Literature Surveymentioning
confidence: 99%